Efficiency Evaluation of Local Government Expenditures Towards The Human Development Index - Ihsanul Ikhwan (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2021)
The purpose of this study was to analyze the efficiency of government expenditure based Human Development Index (HDI) in Local Government at the Indonesian’s Province using Data Envelopment Analysis (DEA) and Tobit Regression. DEA method used to measure the efficiency of a government entity by using multi-input and multi-output. DEA result also can be used to identify which input or output must be evaluated so that Decision Making Unit (DMU) can increase its efficiency. While tobit model was conducted to investigate the connection of the efficiency result to some variables such as population, size, and differences between Java or non-Java provinces The Result from this research showed that Yogyakarta, Jakarta, Central Java, and East Kalimantan were the most efficient provinces in 2015-2018, while East Java was the most inefficient. This research also indicates that education sector was the main source inefficiency both in input and output variables. Tobit analysis showed that all independent variables used in this study had a significant effect on efficiency. Population and size variables had a negative significant effect on the efficiency, otherwise dummy variables of Java and non-Java has positive significant effect to the efficiency achievement. Keywords: Public Expenditure Efficiency; HDI; DEA; Tobit JEl Classification : D24, H72, H75